PENGEMBANGAN KREATIVITAS SISWA DALAM PEMBELAJARAN DI MI MA’ARIF NU 01 PAGERAJI KECAMATAN CILONGOK KABUPATEN BANYUMAS - Abu Dharin (IAIN Purwokerto, 2015)
Abstract: The results showed that: The efforts that teachers in developing students' creativity in the leaming process are: a) Giving full freedom to students in leaming, for example, provide an opportunity to ask questions, ideas and suggestions; b) Creating a leaming atmosphere that is comfortable and pleasant, c) Teacher appearances are democratic, friendly, patient, fair, consistent, flexible, cheerful, humorous, intimate, and always pay attention to all students; d) The teacheralways motivate students to be active in leaming and help them with leaming difficulties; e) Teachers often use a variety of leaming methods so that students are not saturated in the leaming process. f) Teachers use a variety of instructional media that is easy to understand the material presented and the students can visually stimulate students. 2) Teachers also try to create a conducive leaming environment design so that the leaming process can run effectively and efficiently. 3) In the process of leaming that support the creativity of the students do various activities, namely: motor activity, oral activity, the activity of listening, and writing activities. The student activity varied use is that the students are not saturated in leaning activities. Keywords: Creativity Development, Learning